Phytotherapeutic Hierarchical PCL-Based Scaffolds as a Multifunctional Wound Dressing: Combining 3D Printing and Electrospinning - Ünalan, Irem; Slavik, Benedikt; Büttner, Andrea; Boccaccini, Aldo R. (Macromolecular Bioscience, 2024)
This study focuses on developing hybrid scaffolds incorporating phytotherapeutic agents via a combination of three-dimensional (3D) printing and electrospinning to enhance mechanical properties and provide antibacterial activity, in order to address the limitations of traditional antibiotics. In this regard, 3D-printed polycaprolactone (PCL) struts are first fabricated using fused deposition modeling (FDM). Then, alkaline surface treatment is applied to improve the adhesion of electrospun nanofibers. Finally, peppermint oil (PEP) or clove oil (CLV)-incorporated PCL-gelatin (GEL) electrospun nanofibers are collected on top of the 3D-printed PCL scaffolds by electrospinning. Incorporating PEP or CLV into PCL-GEL electrospun nanofibers enhances the scaffold's layer detachment and adhesion force. In addition, the DPPH free radical scavenging activity assay indicates that incorporating PEP or CLV improves the antioxidant properties of the scaffolds. Further, antibacterial activity results reveal that PEP or CLV incorporated scaffolds exhibit inhibition against Staphylococcus aureus and Escherichia coli bacteria. Moreover, anti-inflammatory assays show that scaffolds reduce the concentration of nitric oxide (NO) released from Raw 264.7 macrophage-like cells. On the other hand, the phytotherapeutic hierarchical scaffolds have no toxic effect on normal human dermal fibroblast (NHDF) cells, and PEP or CLV enhance cell attachment and proliferation. Overall, incorporating natural phytotherapeutic agents into hierarchical scaffolds shows promise for advancing wound healing applications.
CRIS-Team Scopus Importer:2024-09-20
Keywords: 3D printing; electrospinning; essential oils; hierarchical scaffolds; wound healing